Primary and Metastatic Liver Tumors Treatment Strategy and Evolving Therapies (Springer International Publishing, 2018)
The incidence of primary and metastatic liver tumors is rising and the therapeutic armamentarium for these tumors is expanding at a rapid pace. As surgery remains the primary treatment modality for these tumors, this book provides a comprehensive, state-of-the art review of the current state of surgical, locoregional and systemic therapy options for malignant liver tumors. It serves as a valuable resource not only for surgeons, oncologists, and clinicians but also for researchers with an interest in malignant liver tumors. Chapters focus on the therapeutic approach to primary and metastatic tumors, providing an up-to-date review on surgical approach, new imaging techniques, patient selection, and technical considerations for liver resection and transplantation. In addition, the text provides new insight into novel and evolving therapies in the areas of advanced surgical techniques and liver-directed arterial based and ablative therapies. Written by experts in their fields, new and evolving approaches in diagnosis and treatment are described and lend insight into contemporary knowledge. Primary and Metastatic Liver Tumors: Treatment Strategy and Evolving Therapies serves as a useful resource for clinicians and researchers managing and treating patients with these challenging malignancies, and provides a concise yet comprehensive summary of the current status of the field that guides patient management and stimulate investigative efforts.